Longitudinal assessment of physical performance in soccer players by internal and external load - Teixeira, José Eduardo (2021)
The training load and recovery status has been assessed to ensure appropriate training and intensity levels in team sports. The training load quantifications can be breakdown in external load and/or internal load, providing insights about the dose-response. The external load is defined as the performed work, such as speed and covered distance, regardless the internal characteristics. Otherwise, the internal load reveals the training physiological and psychological stress. The current research project intends to assess fatigue and recovery levels by internal and external load. This is a longitudinal design (2 years), following-up the training mesocycles in U-15, U-17 and U-19 football players. The evaluation includes five season phases: (1) pre-season (or baseline); (2) beginning of the season (in-season or mid-phase); (3) half of the mid-phase; (4) end of mid-phase; (5) post-season. Each mesocycle corresponds to two weeks and each week represents a microcycle. Heart rate (HR) assess will be performed at 5 Hz intervals using short-range radio telemetry (Polar RS800cx®). The external load measures will be obtained by the global 10 Hz global positioning systems (GPS) devices (STATSports Apex®) with 100Hz tri-axial accelerometers. The perceived exertion will be evaluated after each training session and match-play, through the rating of perceived exertion (RPE) scale. The measurement of accumulated fatigue will be obtained by Total Quality of Recovery (TQR) scale, before each training session or match-play. The fatigue levels will be based on: postexercise recovery heart rate (HRR), heart rate variability (HRV), HR-RPE ratio and neuromuscular fatigue. HRR will be calculated by the difference between HR at the end of training/match-play and the registered HR after 60 seconds of recovery. The fatigue levels will be assessed by the HR variability. Altogether, it is intended to assess the training loads variation between trainings and intra-training (exercise and training phases) over the different season phases.